2012
DOI: 10.2754/avb201281020091
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to canine babesiosis in the Czech Republic

Abstract: From March to November 2010, a total of 68 samples of blood from 41 hunting and working dogs that never left the Czech Republic were examined. Some dogs were sampled repeatedly. Blood samples were examined by polymerase chain reaction for the presence of DNA of piroplasms with negative results. Specific IgG antibodies against Babesia canis were detected by indirect immunofluorescence test, and five dogs (12.21%) were seropositive. Titres ranged from 50 to 200. One dog was positive in two samplings within 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Until recently, babesiosis caused by B. canis was reported frequently in the CR but only as an imported disease [ 98 , 99 ]. Then, in a group of 41 non-traveling dogs from the South Moravian region, 12% of the dogs tested seropositive, although the DNA of B. canis was not detected either in the examined dogs or in 340 questing D. reticulatus ticks collected in the region [ 100 ]. South Moravia, in the southeastern region of the CR, has been known for over 50 years to be an endemic area for D. reticulatus [ 101 , 102 ], and ticks of this species were found in 2009–2010 in numerous localities in South Moravia [ 103 ].…”
Section: Central Europementioning
confidence: 99%
“…Until recently, babesiosis caused by B. canis was reported frequently in the CR but only as an imported disease [ 98 , 99 ]. Then, in a group of 41 non-traveling dogs from the South Moravian region, 12% of the dogs tested seropositive, although the DNA of B. canis was not detected either in the examined dogs or in 340 questing D. reticulatus ticks collected in the region [ 100 ]. South Moravia, in the southeastern region of the CR, has been known for over 50 years to be an endemic area for D. reticulatus [ 101 , 102 ], and ticks of this species were found in 2009–2010 in numerous localities in South Moravia [ 103 ].…”
Section: Central Europementioning
confidence: 99%
“…B. canis was previously reported from the CR; however, all cases were in dogs with a history of travel to endemic areas (Kucera 1992;Svobodova and Svobodova 2004). The most recent study failed to detect parasite DNA in non-travelling dogs or in ticks from the Czech Republic, but did report serologically positive individuals (Konvalinova et al 2012). Our study provides PCR confirmation of B. canis in non-traveling dogs from the South Moravian region, which was suspected as a potentially endemic area with well-established populations of D. reticulatus , having spread from the Panonian lowlands of north-east Austria and western Slovakia.…”
Section: Resultsmentioning
confidence: 91%
“…The permanent presence of D. reticulatus in southern Moravia , together with a number of imported cases raised concerns that B. canis may become established as an endemic pathogen in this part of the CR. In a study performed by Konvalinova et al (2012) on a group of 41 non-travelling dogs and 340 adult unfed D. reticulatus from the South Moravian region, the authors did not detect the parasite by PCR, but found 12% of dogs to be serologically positive.…”
mentioning
confidence: 99%
“…The small babesia of dogs originated from North American and Asian countries, spread to other parts of the world (Teodorowski, 2020), and belong to different genetically distantly related species (Zahler et al, 2000). While B. rossi is one of the most pathogenic species, B. canis is the most common cause of babesiosis (Konvalinova et al, 2012). In Nigeria, B. canis rossi (Takeet et al, 2017) and B. canis vogeli (Sasaki et al, 2007;Adamu et al, 2014) have been reported in dogs.…”
Section: Introductionmentioning
confidence: 99%